Helper system for managing Alzheimer's people using mobile application - Lim, Say Choon (2015)
Alzheimer’s disease is one of the common types of chronic disease and makes the patients easier to lose memory. The effects of this disease will decrease the ability and quality of Alzheimer’s people daily life and increase the dependent or needed others or technology to assist them. Thus this study was focusing on developing helper system for managing Alzheimer’s people using mobile application. This mobile application was developed using Android based platform. It includes the audio reminder that can help to remind the Alzheimer’s people to do their daily life activities on time. While the caregivers can directly remote control and setting the smart phone that taking by Alzheimer’s people and check back the history of the done activities by using computer. Evaluation and validation was performed based on the functionality, user-friendly and acceptability. Result shown that almost 90% of the user agreed and accept that this application is useful for managing Alzheimer’s people and 85% from them agreed that this application had enough functionality, while 10% of the user disagreed and dissatisfied with this application. The recommendation had been made by user on user interface such as with different theme styles to let it more attractive and embedding server application inside the system in order to improve this helper system for future research.